Effect Product Quality, Service Quality and Price on Consumer Purchasing Decisions of the Padang Ampera Uni Restaurant in Pinang City - Alwi Nasution; Ade Parlaungan Nasution; Meisa Fitri Nasution (Universitas Batanghari Jambi, 2023)
This study aims to determine the effect of product quality, service quality and price on consumer purchasing decisions at Padang Ampera Uni Restaurant in Pinang City. Data collection was carried out by distributing questionnaires and distributing them to 100 research samples, namely uni ampere consumers. Data analysis in this study used the help of smart pls 3. Data testing techniques were carried out in partial and simultaneous testing. The results of the analysis show that overall the independent variables have a positive and significant influence on the dependent variable. This can be seen from the value of all t counts that have a higher value than t table with a significant value below 0.05. Overall, the final result of the study is that the independent variables gives an effect of 0.573 or 57.30% and the rest is influenced by other supporting factors.